A Comparison Between Pressure Wire and Microcatheter Measurements for Evaluating the Cerebral Venous Pressure Gradient - Horev, Anat; Lorber, Dana; Vardi-Dvash, Noa; Zlotnik, Yair; Biederko, Ron; Ifergane, Gal; Shelef, Ilan; Zvenigorodsky, Vladislav; Horev, Amir (Frontiers in Neurology, 2021)
Introduction: A pressure gradient of over 8 mm Hg across the stenosis (usually located in the transverse-sigmoid junction) is one of the criteria for cerebral venous stenting in idiopathic intracranial hypertension (IIH) patients. The possible inaccuracy of the traditional microcatheter-based pressure measurements has been discussed in previous studies. In the cardiology field, a dual-sensor pressure wire is routinely used for the evaluation of stenotic lesions. Using a pressure wire for cerebral vasculature was previously discussed in a small case series and case reports. In this study, we compared venous pressure measurements obtained using both a microcatheter and a pressure wire in patients who were candidates for stenting. Methods: A retrospective study was conducted, comparing the two methods of pressure measurements in 26 patients with venous stenosis. Altogether, 120 measurements were performed using both methods. Demographic characteristics, medical history, procedural details, medications, indications for the procedure, and complications were collected from the patient charts. Results: Based on an 8-mm Hg pressure gradient cutoff indication, 19 patients were found eligible to go through unilateral venous stenting based on catheter measurements alone. The wire results corroborated the catheter results in detecting all cases indicated for a stent. This finding implies a sensitivity equal to 100% for the wire measurements. There were no wire-related complications, demonstrating its safety. Conclusions: We conclude that the pressure wire is as safe as the microcatheter and can identify cases requiring intervention. A larger-scale study is needed to assess the measurement accuracy of the pressure wire in brain vasculature.